Epidemic Projections and Opportunities to Accelerate Control of Tuberculosis in Mozambique : Findings from an Optima Modelling Analysis - World Bank (World Bank, Washington, DC, 2021)
Mozambique is one of the thirty highest tuberculosis (TB) burden countries in the world with respect to total incidence. Active case finding programs in Mozambique have been expanding, and community-based efforts now account for around twenty-five percent of detected cases. This involves both contact tracing of notified cases and other community-level interventions such as active house-to-house screening and testing, mobile van outreach in TB hotspots, and screening and testing of community health workers. However, there are opportunities for further expansion. This policy brief summarizes the findings of an allocative efficiency analysis using the Optima TB model, and highlights opportunities to maximize the impact of TB spending in Mozambique.